Um analisador quimiluminescente em fluxo-batelada baseado em filmes digitais com extração em fase sólida magnética aplicado a determinação de cobre em cachaças - Andrade, Renato Allan Navarro (2017)
This work proposes a full methodology for determination of copper (II) ions in spirits. The methodology consists in three steps: (1) chemical adsorption of the analyte in magnetite (Fe3O4) nanoparticles covered aluminium oxide and fuctionalized with with sodium docecyl sulfate and 1-(2-pyridylazo)-2-naphthol ; (2) desorption of the analyte in acid médium and (3) detection of the analyte by means of its catalytic effect over the chemiluminescent reaction between luminol and hydrogen peroxide (H2O2). The first two steps are carried out in automatic manner using a flow-batch analyzer specially designed for this aim, as the detection was carried out from digital movies inside the automatic system. After synthesis, magnetic nanoparticles were characterized by X-Ray Diffraction and Scanning Electron Microscopy which indicated particle sizes in the order of nanometers with uniform distribution of sizes, respectively. The flow-batch automatic system has an especial mixing chambre in polytetrafluorethylene with a quartz circular window for on-line recording of the chemiluminescent phenomenon by digital films. Coupled to it, a robotic device with neodymium magnets was used in order to generate magnetic fields. The whole process was managed by a software written in ActionScript 3.0. Digital movies have been recorded at a rate of 30 frames per second. Analytical curves have been obtained by means of the concept of norm of the vector in the space RGB color system. The significant experimental factors over the analytical response were studied and optimized by means of factorial design and response surface methodology, respectively. The definitive methodology allowed to estime limit of detection and quantification of 3.73 e 22.4 ?g L-1 of Cu(II) ions, respectively. Accuracy was assessed in terms of recovery tests whose rates were between 95 and 106% in actual spirit samples. Such performance characteristics are a reasonable indicative of the feasibility of the proposed methodology for monitoring copper (II) ions contente in the mentioned beverage.